2020
DOI: 10.1093/cercor/bhaa280
|View full text |Cite
|
Sign up to set email alerts
|

Increased Callosal Connectivity in Reeler Mice Revealed by Brain-Wide Input Mapping of VIP Neurons in Barrel Cortex

Abstract: The neocortex is composed of layers. Whether layers constitute an essential framework for the formation of functional circuits is not well understood. We investigated the brain-wide input connectivity of vasoactive intestinal polypeptide (VIP) expressing neurons in the reeler mouse. This mutant is characterized by a migration deficit of cortical neurons so that no layers are formed. Still, neurons retain their properties and reeler mice show little cognitive impairment. We focused on VIP neurons because they a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…In a complementary condition, the S1 VIP-expressing neurons lost their preferential abundance in the superficial layers. Moreover, the long-range inputs onto VIP-expressing neurons from ipsilateral and contralateral cortices were compromised, contributing to a dysfunctional elaboration of the incoming inputs ( Hafner et al, 2021 ). In addition, Goff and Goldberg (2019) have shown that the neocortical VIP-expressing neurons in Scn1a +/– mice, a mouse model of Dravet syndrome, exhibited impaired excitability.…”
Section: The Role Of Vip-expressing Neurons In Cortical Dysfunctionmentioning
confidence: 99%
“…In a complementary condition, the S1 VIP-expressing neurons lost their preferential abundance in the superficial layers. Moreover, the long-range inputs onto VIP-expressing neurons from ipsilateral and contralateral cortices were compromised, contributing to a dysfunctional elaboration of the incoming inputs ( Hafner et al, 2021 ). In addition, Goff and Goldberg (2019) have shown that the neocortical VIP-expressing neurons in Scn1a +/– mice, a mouse model of Dravet syndrome, exhibited impaired excitability.…”
Section: The Role Of Vip-expressing Neurons In Cortical Dysfunctionmentioning
confidence: 99%
“…This neuronal subtype readily populates the corpus callosum, playing an essential role in interhemispheric connection (Pesold, Impagnatiello et al 1998). This process has been recently associated with Reelin signaling (Hafner, Guy et al 2021),suggesting that local Reelin secretion could participate in the maintenance of axonal tracks in the corpus callosum.…”
Section: Roles Of Apoer2 In the Axon In The Context Of Reelin Signalingmentioning
confidence: 99%